Removal of Radioactive Iodide by Surfactant-Modified Zeolites - Hossein Faghihian; Akbar Malekpour; Mohammad G. Maragheh (Adsorption Science & Technology)
The removal of radionuclides such as 129 I and 131 I from radioactive liquid wastes was studied. Two natural zeolites were modified with different quaternary alkylammonium ions to replace the exchangeable cations from the zeolite surface and used as adsorbent materials. The quaternary ions used for such purpose were hexadecyltrimethylammonium, tetradecyltrimethylammonium, dodecyltrimethylammonium, tetrabutylammonium and tetramethylammonium, respectively. Some of the modified forms exhibited an adsorption capacity much higher than those of the respective natural samples. In contrast, the adsorption capacity was negligible when tetrabutylammonium and tetramethylammonium ions were used. Adsorption experiments were conducted by batch and continuous experiments, and adsorption isotherms constructed from the data obtained. The effect of interfering anions on the adsorption capacity was also investigated as were the breakthrough behaviours of radioiodide in a column charged with the various adsorbents. Desorption of iodide from the modified zeolites into different solutions was also investigated. It was concluded that, in some cases, surfactant modification was an efficient process for the uptake and immobilization of iodide.